Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given $G$, $H$, $G'$, and $H'$ are cyclic groups of orders $m$, $n$, $m'$, and $n'$ respectively.

If $G*H$ is isomorphic to $G'* H'$, I would like to show that either $m = m'$ and $n = n'$ or else $m = n'$ and $n = m'$ holds. Where * denotes the free product.

My approach:

$G*H$ has an element of order $n$, thus $G' * H'$ has one too.

But already the next step is not clear to me, should I show that there is an element of length $> 1$ which has infinite order or what would be the right approach here?

Thank you.

share|improve this question
1  
In group theory, $\ast$ means the free product. Did you mean that, or did you mean $\times$, the direct product? –  Zev Chonoles Dec 15 '11 at 0:41
5  
Do you know that all elements of finite order are conjugate to an element of either $G$ or $H$? That should help show the first part. Now also prove that the if $K$ is the normal closure of $H$, then $(G*H)/K\cong G$. –  user641 Dec 15 '11 at 0:49
1  
yes I ment the free product –  Jake Dec 15 '11 at 0:51

2 Answers 2

It is a theorem of Schreier that any element of $G*H$ that has finite order must be conjugate to an element of $G$ or an element of $H$. (This is what Steve D notes in his comment).

To see this in the special case where $G$ is cyclic of order $n$ and $H$ cyclic of order $m$, let $G=\langle g\rangle$ and $H=\langle h\rangle$. Let $w$ be a reduced word in $G*H$ and assume that it is of finite order. Without loss of generality, let's say that it starts with $g$. Then we have $$w = g^{a_1} h^{b_1} \cdots g^{a_k}h^{b_k}$$ where $0\lt a_i\lt n$ for each $i$, and $0\lt b_i\lt m$ for $i=1,\dots,k-1$, with $0\leq b_i\lt m$.

If $b_k\gt 0$, then the length of $w^r$ is $2rk$, as there are no cancellations; so $w$ cannot be of finite order. Thus, $b_k=0$, and we have $$w = g^{a_1}h^{b_1}\cdots h^{b_{k-1}}g^{a_k}.$$ We can then conjugate $w$ appropriately so that either $a_i=0$ or $a_k=0$ (or both). Repeating the argument, we see that we must actually have $a_1+a_k = n$, so that $w$ is conjugate to $h^{b_1}g^{a_2}\cdots g^{a_{k-1}}h^{b_{k-1}}$. Now repeat the argument conjugating; eventually, we will end up with $g^{a_i}$ or $h^{b_j}$, so $w$ is conjugate to an element of $H$ or to an element of $G$.

So assume that $G*H\cong G'*H'$. Without loss of generality say $m\leq n$ and $m',n\leq n'$. If $n\lt n'$ we have a contradiction, since $G'*H'$ has an element of order $n'$, but every element of finite order in $G*H$ has order dividing $n$ or $m$. So $n=n'$, as desired.

Now we need to show that $m=m'$. We may assume $m\leq m'$.

The universal property of the coproduct tells us that the identity map $G\to G$ and the trivial map $H\to G$ induce a homomorphism $G*H\to G$ which restricts to the identity on $G$ and to the zero map on $H$. The kernel is then exactly the normal closure of $H$ of $G*H$, $K$; in particular, the normal closure of $H$ intersects $G$ trivially. Symmetrically, the normal closure of $G$ in $G*H$ intersects $H$ trivially.

The isomorphism $G'*H'\to G*H$ maps the generator of $H'$ to a conjugate of an element of $H$ or of $G$; and maps the generator of $G'$ to a conjugate of an element of $H$ or of $G$. But they cannot both map to conjugates of elements of $H$, or both to conjugates of elements of $G$: because then the map $G*H\to G$ (respectively, the map $G*H\to H$) would be a nonzero map, but when composed with the isomorphism $G'*H'\to G*H$ we would get the zero map, which is impossible. So if the generator of $H'$ maps to a conjugate of an element (in fact, a generator) of $H$, then the generator of $G'$ must map to a conjugate of an element of $G$, which proves that $|G'|\leq |G|$. This proves equality, since $m\leq m'$. If the generator of $H'$ maps to a conjugate of an element of $G$ then $n'\leq m\leq n=n'$, so we must have $n=m=n'=m'$.

share|improve this answer

Let me give you an alternative argument for the claim $m=m'$ in Arturo Magidin's answer.

Take the abelianizations of the groups $G*H$ and $G'*H'$, since $G,G,H,H'$ are abelian, their abelianizations are $G\oplus H$ and $G'\oplus H'$ respectively. Then you get $G\oplus H\cong G'\oplus H'$ and in particular, their orders $mn=m'n'$ are equal. Since we already had $n=n'$, we conclude that $m=m'$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.